Morphology and dielectric properties of Ni0.5Zn0.5Fe2O4 nanoparticles prepared via mechanical alloying technique - Hassan, Rafidah (2014)
Ni-Zn spinel type ferrites are interesting materials due to its electrical and semiconductor properties. These materials are widely used and exploited. Nickel-zinc ferrite nanoparticles are very important soft magnetic materials for high and low frequency devices application and are good dielectric materials. The starting powders with nanoparticle-size of approximately 22 nm of as-milled Ni0.5Zn0.5Fe2O4 were obtained by mechanical alloying. The effect of sintering temperature on the evolving microstructural of a single sample Ni0.5Zn0.5Fe2O4 with the dielectric properties was investigated. The single sample pellet was subjected to repeat sintering from 600oC to 1200oC with 50°C increments. The ferrite sample was analyzed by X-Ray diffraction (XRD) to investigate the phases of the powder and Field Emission Scanning Electron Microscope (FESEM) for the morphology and microstructure analysis. The dielectric properties of the sample were measured using HP 4192A LF Impedance Analyzer in the low frequency range from 40 Hz to 1 MHz and measuring temperatures ranging from 30 oC to 250 oC. The study of dc conductivity on nickel zinc ferrite nanoparticles pellet was carried out to analyze the mechanism of conduction and temperature dependence by using a computer controlled Keithley 236 Source. The variation with temperature of dc conductivity were done from 30°C to 250°C for different sintering temperatures 600°C to 1200°C at 100°C intervals. The results from XRD show that single phase Ni0.5Zn0.5Fe2O4 could not be formed during milling alone and therefore requires sintering. It also confirms that the single sample sintered Ni-Zn ferrite has single phase cubic spinel structure with lattice parameter 5.3273 Å and the formation of single phase crystallization Ni0.5Zn0.5Fe2O4 was detected at early sintering temperature of 600°C exhibiting the advantage of mechanical alloying. The crystallization of the ferrite sample increase with increasing sintering temperature and it was found that there is more densification or less porosity at the higher sintering temperature. The FESEM micrograph shows a significant difference in grain size distribution from 88 nm to 646 nm with increasing sintering temperature from 600°C to 1200°C. This might be an indication for different mechanisms being responsible for grain growth with respect to temperature. Evolution of the microstructure resulted in three activation energies of grain growth where above 850°C, there is a rapid grain growth in the microstructure. The activation energies of grain growth increased with rise in sintering temperature as the average grain size increased from nano-size to micron-size. The variation of the dielectric constant and dielectric loss factor as a function of frequency for the ferrites system at different temperatures show that both the dielectric constant and dielectric loss factor decreases with increasing frequency which is a normal dielectric behavior of spinel ferrites. The Cole-Cole plots are an essential tool for studying the dielectric behavior. It reveals two primary relaxation mechanisms in operation for all sintering temperatures indicating a non-debye relaxation type. Arrhenius diagram of relaxation time as a function of reciprocal temperature is used to analyze the effect of temperature on the rates of chemical reactions. The activation energies of dielectric relaxation decreased with rise in sintering temperature. The activation energy affects the hopping mechanism which correponded with the electrical energy barrier encountered by the electrons during the hopping process. The study of dc conductivity on nickel zinc ferrite nanoparticles was carried out to analyze the mechanism of conduction and the temperature dependence. The values of electrical conductivity σdc increased with increasing temperature indicating the semiconducting behavior of the sample due to the increase in the thermally activated drift mobility of the charge carriers.